Pengembangan dan Validasi Metode Spektrofotometri Area Under Curve Untuk Campuran Biner Parasetamol dan Ibuprofen Dalam Bentuk Sediaan Tablet - Rida Evalina Tarigan; Lutvia Lutvia; Rina Monica Taruliana Sitorus (Fakultas Farmasi Universitas Setia Budi, 2022)
The combination of paracetamol (PAR) and ibuprofen (IBU) is the most commonly used over-the-counter medication for fever and pain. This study aimed to develop spechtrophotometry method by area under curve to determine the levels of PAR and IBU in tablet dosage form. This method is based on the area under the curve value of each spectrum in various concentrations is calculated to selected wavelength range analysis, with methanol as solvent. Then, this method was applied to determine levels of PAR and IBU in tablet dosage form. The result of this method is the analysis of selected wavelength ranges of PAR and IBU in the wavelength ranges of 244-254 nm and 220-230 nm, respectively. The mean % recoveries were found to be in 99.35% and 99.49% for PAR and IBU, respectively. The method is successfully applied to determine PAR and IBU in tablet dosage form simultaneously and fulfill the validation requirements.